The Use of The Pavlonii Series for Landscaping the Surroundings of the City - Шайманов Шерзод Камол угли; Файзуллаев Уткир Аминкулович; Бердиева Шахрзода Ибодулло кизи (Web of Journals Publishing, 2023)
Paulownia is widely used for landscaping urban landscapes, in landscape gardening, to create recreation areas. In addition, due to the large area of leaf plates, paulownia successfully purifies the air even in the most polluted and gassed areas, and its root system cleanses the soil of heavy metal salts.
Keywords: paulownia, tree, flowers, seeds, fragrance, landscaping, scenery, plantations, recreation area, culture.